Mobile Recommendations for Shopping Mall Customers - Carvalho, Gustavo D.; Silva, Renato S.; Durão, Frederico A.; Silva, Diogo Vinícius de S (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2016)
Advances in technology allows us to carry a computer in our pockets. Smartphones are a tendency and almost mandatory to anyone living in an urban and modern context. Considering this, we realize malls are indispensable to our society. Nevertheless, with hundred of stores and products, people tend to loose themselves or to waste a lot of time finding something in the midst of its hugeness. This paper proposes a model to assist and to recommend customers to find what they consider relevant at malls. Using a mobile application, InMap, the model does recommendations based on user activities and they rely on content-based techniques that provide the most relevant results.